(untitled) (Journal of Business Management and Accounting, 2011)
Despite the inherent liability of resource scarcity, superior performance of small and medium enterprises in foreign market operations has made the study of small firm internationalization a focus of many scholars. Although investigation into the phenomenon abound, the complexity of international business generates intricacy into the research process. This paper discusses an investigation grounded on the composite of Internationalization Models, namely the Uppsala MODEL and the Resource-based view. The explication highlights the critical role of organizational resources and capabilities in leveraging relationship quality with a foreign partner to internationalize at a faster rate. The underlying argument is that a lack of financial and human resources pose a constraint to small businesses to internally generate foreign market knowledge to identify opportunities. Small businesses acquire knowledge by leveraging quality relationship with a foreign partner. This paper conjectures relationship quality as a proxy to the level of knowledge acquisition where the relationship acts as a conduit to information flow. Finally, a conceptual model is proposed and several propositions are also suggested.